The Role of Mathematics In Improving The Quality of Education Based on Modern Islamic Civilization - Fatahillah, Axl Ferrari; Dinanti, Shafa Desliana; Amrillah, Rizki (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Mathematics is one of the fields of study that has a crucial role in improving the quality of education. Islamic society attaches importance to the understanding of mathematics because of efforts to create a modern society that is by the development of sophisticated times. This study aims to determine the role of mathematics in improving the quality of education based on Islamic civilization. This study used descriptive qualitative research with a literature research approach. Literature research is a form of study conducted to collect information and data by utilizing various types of material available in libraries. The research material used in this study was obtained from relevant journal documents. Through the literature study method, researchers collect references to previous articles then sort, select and combine them so that answers to research questions and conclusions are obtained The result of this study is that students can integrate education, especially the role of mathematics with Islamic values. The gap in this study is the role of mathematics in education. The novelty in this study is how mathematics in modern Islamic civilization